The Key Characteristics of Food Blogger to Create Purchase Intentions in Indonesia - Adinda MelodieBestari, Jacqueline Simon, 3Lim Sanny (International Journal of Advanced Science and Technology, 2020)
This study examined how social media influencers (SMIs), specifically food bloggers, triggered purchase intentions through consumers’ desire to mimic as a mediating variable. It was expected to find the key characteristics of food bloggers which need to be considered to select the most effective food bloggers. In our hypotheses, 5 characteristics which included attractiveness, expertise, informativeness, interaction and likability are positively related with consumers’ desire to mimic, followed by consumers’ purchase intentions. 164 Instagram users domiciled in Indonesia participated in our online survey, but only 162 responses were valid. 3 questions which originally used to measure the constructs were also taken out due to invalidity issues. Our results showed that only four (attractiveness, expertise, interaction and likability) out of five food bloggers’ qualities have positively affected consumers’ desire to mimic with significant result, following with purchase intention. The only food bloggers’ quality which does not affect consumers’ mimicry desire is informativeness. The benefits of this study for scholars and practitioners were discussed.